(untitled) (Research, Society and Development, 2024)
Respiratory failure in pediatrics is a complex condition that represents a significant challenge for healthcare professionals dealing with pediatric patients. In this context, it is crucial to develop a comprehensive understanding of all aspects related to this syndrome, from its etiology to the most effective management strategies. This condition encompasses a wide spectrum of respiratory disorders, which can be congenital, acquired, or iatrogenic in nature. Therefore, this study aims to investigate the available scientific evidence on respiratory failure in pediatrics, its causes, clinical manifestations, diagnostic methods, and management strategies. It is an integrative literature review; the methodology involved a thorough search in electronic databases, including PubMed, to identify relevant studies published in the three years prior to the current date (2024, 2023, 2022). The specific MESH descriptors used were "Respiratory Insufficiency," "Pediatrics," "Syndrome," "Treatment," and "Diagnosis." The search resulted in a total of 125 relevant articles. Further research is needed to address knowledge gaps, standardize diagnostic criteria, and optimize therapeutic strategies tailored to the unique needs of pediatric patients with respiratory failure.